Expedition work in the central part of the Kamchatka East Volcanic belt and in the Kamchatka River valley in 2023 - E.G. Kalacheva (Вестник Камчатской региональной ассоциации "Учебно-научный центр". Серия: Науки о Земле, 2024)
This article provides a brief description of the expedition work conducted by the staff of the Institute of Volcanology and Seismology, FEB RAS, in the central part of the Eastern Volcanic belt of Kamchatka, and in the Kamchatka River valley in the Summer-Autumn of 2023. In order to study the conditions for the formation and discharge of thermal waters of large volcanic centers, to estimate the hydrothermal discharge of magmatic volatiles (primarily CO2), hydrochemical and gas testing was carried out on the thermal fields of the Kikhpinych and Bolshoi Semyachik volcanic massifs, and in the Uzon caldera. In parallel with geochemical sampling, aerial and infrared photography of thermal sites was carried out. To determine the degree of influence of volcanic and hydrothermal activity on the ion runoff into the Pacific Ocean, hydrochemical and hydrological works were carried out in the Kamchatka Riverv alley. A comprehensive study of unique alkaline cold springs was carried out in the Belaya River valley (Kamchatsky Peninsula). A large number of water and gas samples, sediments and mineral salts were collected for further analytical studies during the expedition works.